HUBUNGAN BODY MASS INDEX (BMI) DENGAN DISMENOREA PRIMER DI SLTP NEGERI 2 KEMANGKON KABUPATEN PURBALINGGA - Adriani, Prasanti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Women in the teenage stage who experience menstrual disorders are around 75%. These risk factors include age of early menarche, family history of complaints of dysmenorrhea, abnormal Body Mass Index (BMI), fast food eating habits, menstrual bleeding duration, exposure to cigarette smoke, consumption of coffee and alexythimia. The preliminary study conducted by researchers on April 4, 2018 on 20 young women in SLTP Negeri 2 Kemangkon, obtained 15 young women who experienced menstrual pain during menstruation and 5 young women, including with overweight Body Mass Index (BMI) status, and 7 teenage girls. Skinny Mass Index (BMI), while 3 young women who did not experience menstrual pain with normal Body Mass Index (BMI). The purpose of this study was to determine the relationship of Body mass index (BMI with dysmenorrhea in female students at SLTP Negeri 2 Kemangkon. This research is quantitative analytical with a retrospective approach. Data analysis used is univariate analysis and bivariate analysis. The sampling technique uses total sampling technique, with the number of samples in this study is 69 respondents. The output of this study is the ISSN national scientific article and the instructional material on reproductive health midwifery care. The results of this study were the most frequent BMI (Body Mass Index) of respondents were 41 respondents (59.4%), the respondents who experienced primary dismenor were 60 respondents (87%). Chi-Square test results obtained p-value 0.469. This number means that there is no correlation between body mass index (BMI) and primary dysmenorrhea in Kemangkon State Junior High School 2 students in 2018. Keywords: Body Mass Index (BMI), Primary Dismenorrhea.